Antibiotic Use and Stewardship Practices in a Pediatric Community-based Cohort Study in Peru: Shorter Would be Sweeter. (24th June 2022) - Schiaffino, Francesca; Colston, Josh M; Paredes Olortegui, Maribel; Rengifo Pinedo, Silvia; Zamora Babilonia, Marcelo; Ramal Asayag, Cesar; Peñataro Yori, Pablo; Kosek, Margaret N
Abstract: Background: There is a need to evaluate antibiotic use, duration of therapy, and stewardship in low- and middle-income countries to guide the development of appropriate stewardship programs that are global in scope and effectively decrease unnecessary antibiotic use. Methods: We prospectively collected information on illness occurrence and antibiotic use from a cohort of 303 children. We evaluated the incidence, duration of therapy, and appropriateness of antibiotic prescriptions by 5 main antibiotic prescribers (physicians and nurses, pharmacists, nursing assistants, self-prescriptions, and neighbors or family members). Results: Ninety percent of children received an antibiotic during follow-up, and on average, by the end of follow-up a child had spent 4.3% of their first 5 years of life on antibiotics. The most frequent prescribers were physicians/nurses (79.4%), followed by pharmacists (8.1%), self-prescriptions (6.8%), nursing assistants (3.7%), and family or neighbors (1.9%). Of the 3702 courses of antibiotics prescribed, 30.9% were done so for the occurrence of fever, 25.3% for diarrhea, 2.8% for acute lower respiratory disease, 2.7% for dysentery, and 38.2% for an undetermined illness. Courses exceeding the recommended duration were common for the principal diseases for which treatment was initiated, with 27.3% of courses exceeding the recommended length duration, representing a potential reduction in 13.2% of days on which this cohort spent on antibiotics. Conclusions: Stewardship programs should target medical personnel for a primary care stewardship program even in a context in which antibiotics are available to the public with little or no restrictions and appropriate duration should be emphasized in this training.